PROBLEMATIKA PEMBELAJARAN SASTRA BERBASIS DIGITAL DI MASA PANDEMI DALAM RUANG LINGKUP STKIP PARIS BARANTAI - Normasunah Normasunah; Andi Muhammad Yahya (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2021)
Digital-based distance education is one of the policies carried out by the government in Indonesia to keep education running. However, in the actualization of digital-based learning, many complaints were found from various groups, especially from students. The purpose of this study is to describe learning media and internet network access that is used as a connector for learning during the pandemic which is a problem in the literary learning process. This study uses a qualitative descriptive method, which describes the problems experienced by students when participating in digital-based literature learning. The results of this study indicate that the problems of digital-based learning are found from various aspects, both from lecturers, students, and aspects of the digital-based learning media used. The description of the problems of digital-based learning in the pandemic period as a result of this research is very useful for the development of teaching creativity. It can be concluded that various aspects of digital-based learning still need to be improved and developed. Lecturers must continue to improve teaching creativity, and learning media still need to be updated. Keywords: Problematic, Digital Teaching, Literature